John Mills and British cinema : masculinity, identity and nation - Plain, Gill (Edinburgh University Press, 2006)
Although his film career extended from the early days of sound to the British New Wave and beyond, Sir John Mills is nonetheless remembered as the archetypal hero of the Second World War. Regarded as an English 'everyman', his performances crossed the class divide and, in his easy transition from below decks to above, he came to represent a newly democratic masculine ideal. But what was this exemplary masculinity and what became of it in the aftermath of war? John Mills and British Cinema asks how was it possible for an actor to embody national identity and, by exploring the cultural contexts in which Mills and the nation became synonymous, the book offers a new perspective on 40 years of cinema and social change. Through detailed analysis of a wide range of classic British films, John Mills and British Cinema exposes the shifting constructions of 'national' masculinity, arguing that the screen persona of the actor is a fundamental, and often overlooked, dimension of British cinema. Key Features: Provides the first critical examination of the film career of Sir John Mills. Uses contemporary feminist and gender theories to examine the body of the actor as a crucial dimension of the film text. Explores the concept of a 'national cinema' from an innovative new perspective. Provides stimulating new readings of key British films, including Forever England, The Way to the Stars, Great Expectations, Scott of the Antarctic, Hobson's Choice, Ice Cold in Alex, Tunes of Glory, The Family Way and Ryan's Daughter.